2017
DOI: 10.1002/acm2.12182
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field dose effects on different radiation beam geometries for hypofractionated partial breast irradiation

Abstract: PurposeHypofractionated partial breast irradiation (HPBI) involves treatment to the breast tumor using high doses per fraction. Recent advances in MRI‐Linac solutions have potential in being applied to HPBI due to gains in the soft tissue contrast of MRI; however, there are potentially deleterious effects of the magnetic field on the dose distribution. The purpose of this work is to determine the effects of the magnetic field on the dose distribution for HPBI tumors using a tangential beam arrangement (TAN), 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…Two previous studies have focused on magnetic field dose effects for postoperative RT in the supine position [26] , [27] . Van Heijst et al investigated the magnetic-field impact on skin dose with WBI (42.56 Gy in 16 fractions, 2-field forward IMRT) and APBI (38.5 Gy in 10 fractions, 7-field IMRT) at 0T, 0.35T and 1.5T [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies have focused on magnetic field dose effects for postoperative RT in the supine position [26] , [27] . Van Heijst et al investigated the magnetic-field impact on skin dose with WBI (42.56 Gy in 16 fractions, 2-field forward IMRT) and APBI (38.5 Gy in 10 fractions, 7-field IMRT) at 0T, 0.35T and 1.5T [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Other OARs were not adversely influenced by the magnetic field. Kim et al analyzed the 1.5T magnetic field dose effects using a tangential beam arrangement, 5-beam IMRT, and VMAT for APBI delivered in 8 fractions of 5 Gy [27] . Heart and lung doses were minimally impacted by the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increase in skin dose for PBI in a magnetic field would be highly unlikely to translate into a higher risk of radiation dermatitis. Furthermore, it has been reported that increasing the number of beam angles helps in decreasing the skin dose (60,62). Therefore, although PBI is a good indication for breast RT on a hybrid machine, one should remain aware of the risk of increased skin dose and use more rather than fewer beams.…”
Section: Electron Return Effectmentioning
confidence: 99%
“…Therefore, although PBI is a good indication for breast RT on a hybrid machine, one should remain aware of the risk of increased skin dose and use more rather than fewer beams. Because the ERE effect is also present at the lung-tissue interface, it is also important to check the maximum lung and chest wall dose (57,62). Previous planning studies concluded that the effects of the magnetic field on OARs, other than the skin, are generally negligible, and doses were within clinical constraints (60,62,63).…”
Section: Electron Return Effectmentioning
confidence: 99%
“…The MR linac is also considerably different to the conventional linac, with mechanical limitations on the collimator, couch, treatment field size and delivery techniques, which change the treatment planning and delivery process for breast radiotherapy. The radiofrequency coils required for MR imaging, associated geometric accuracy and isotropic resolution, and the very presence of a magnetic field during treatment delivery with the effects upon secondary electrons [27][28][29][30], are important factors for dose calculations and affect the dosimetry in the breast. Given longer fraction durations on the MR linac, especially with high dose per fraction prescriptions and the adaptive nature of treatments, intrafraction motion must also be considered.…”
Section: Introductionmentioning
confidence: 99%